Smoking and lifestyle in an urban population - Elkin Martínez L; Liliana Saldarriaga R (Universidad de Antioquia, 2011)
Smoking is harmful for one's health and affects many people in the world. Its consequences are high morbidity and mortality from cardio-respiratory diseases and cancer. This complex public health issue also entails high costs. In order to understand this addiction, it is necessary to find out whether its presence is an isolated habit or a part of an unhealthy behavior. Objective: to explore the relationship between smoking and some components of a lifestyle. Methodology: a cross-sectional study with 4,000 adults aiming at identifying the link between smoking and certain aspects of lifestyle such as age, gender, education, socioeconomic level, physical inactivity, eating habits, recreation and alcohol. Results: age and socioeconomic level were not found to be associated with smoking; however, gender, schooling level, alcohol consumption, physical inactivity, unhealthy eating habits, and inadequate recreation were found to be statistically and epidemiologically related to smoking. Conclusions: smoking is associated with other adverse components of an unhealthy lifestyle. Community control and health promotion activities should address this issue through comprehensive strategies aimed at modifying human behavior in order to achieve more effective results.